Towards Secure Top-k Multi keyword Retrieval over encrypted cloud data - pillai, P.Saranya, Lekshmi k (International Journal of Scientific Research and Management (IJSRM), 2017)
Cloud computing has emerging as a promising pattern for data outsourcing and high-quality data services. However, a concern of sensitive information on cloud potentially causes privacy problems. Data encryption protects data security to some extent, but at the cost of compromised efficiency. To observe that server-side ranking based on order-preserving encryption (OPE) inevitably leaks data privacy. To eliminate the leakage, traditional method uses a two-round searchable encryption (TRSE) scheme that supports top-k multikeyword retrieval. The TRSE method employs a vector space model and homomorphic encryption. The vector space model helps to provide sufficient search accuracy, and the homomorphic encryption enables users to involve in the ranking while the majority of computing work is done on the server side by operations only on cipher text. As a result, information leakage can be eliminated and data security is ensured but, user side Top-K retrieval process is based on user’s click event, sometimes it is difficult to users. So we propose a method for Top-K retrieval. In this method user gets an interested/used link in the top.